LAYER CHARGE AND CHARGE DISTRIBUTION OF SMECTITES: A PARAMETER WHICH CONTROLS IMPORTANT PHYSICAL PROPERTIES OF BENTONITES - Christidis, G. E. (Bulletin of the Geological Society of Greece, 2007)
The new method of Christidis and E beri (2003), which determines the layer charge and charge distribution of dioctahedral smectites in bentonites is presented and is compared to the existing methods for determination of layer charge and charge distribution, namely the structural formula method and the alkylammonium method. The new method is based on the comparison ofXRD traces of K-saturated, ethyleneglycol solvated smectites with simulated XRD-traces calculated for three-component interlayering. Applications of the method include modeling of the evolution of smectite layers towards illite during diagenesis, and study of the influence of layer charge and charge distribution of smectites on important physical properties of bentonites such as rheological properties (viscosity, gel strength, yield point and thixotropy) and swelling. Smectites with layer charge between -0.425 and-0.47 to - 0.48 equivalents phfu affect rheological properties in a different way compared to smectites with higher or lower layer charge than this layer charge interval. Based on these observations a new classification scheme for smectites has been proposed according to their layer charge. In this classification scheme the term smectites with intermediate layer charge has been introduced.